THEORETICAL BASES OF THE ORGANIZATION OF MODERN MEDICAL INFORMATION - TELECOMMUNICATION SYSTEMS - Юдін, О. К.; Ільєнко, А. В.; Зюбіна, Р. В.; Сергеєв-Горчинський, О. О. (Science-based technologies, 2015)
The analysis of modern information and telecommunication systems for medical purposes. The basic directions and scope of the use of telemedicine systems. Terminological system studied domestic and foreign authors. The basic kinds and types of telemedicine information. We consider the standards used for the transmission and processing of medical data. Analyzed in detail the levels and structure of the organization of information and telecommunication systems for medical purposes. Based on the analysis of modern telemedicine information transmission channels allocated based on the parameters: transmission speed, range, prevalence, reliability, cost, portability. Based on the analysis identified further ways to improve the functioning of information - telecommunication systems, medical supplies through the development of modern methods and models of optimal filtering aimed at the qualitative selection of the information signal in a small ratio signal \ noise.